2008
DOI: 10.1016/j.ejca.2008.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Computer aids and human second reading as interventions in screening mammography: Two systematic reviews to compare effects on cancer detection and recall rate

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
0
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(100 citation statements)
references
References 50 publications
2
88
0
8
Order By: Relevance
“…Other studies have suggested limited effectiveness of CAD in mammography (31,32), however the finding that CAD can systematically improve or worsen readers' performance depending on their skill and the difficulty of cases is a novel finding.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested limited effectiveness of CAD in mammography (31,32), however the finding that CAD can systematically improve or worsen readers' performance depending on their skill and the difficulty of cases is a novel finding.…”
Section: Discussionmentioning
confidence: 99%
“…This work has been described in detail elsewhere. 21 Ten studies were found comparing single reading with single reading with CAD, and 17 comparing single reading with double reading. Double reading with arbitration (films where the two initial readers disagree are reviewed by a third) shows a significant increase in detection rate (odds ratio: 1.08, 95% CI 1.02 -1.15) and a significant decrease in recall rate (odds ratio: 0.94, 95% CI 0.92 -0.96).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have validated CAD techniques in screening populations and found a sensitivity ranging from 73 [2] to 96% [3]. Moreover, the impact of a CAD system on the performance of mammogram observers was evaluated in several studies [2,[4][5][6][7][8][9][10][11][12][13][14], showing that there is insufficient evidence to claim that CAD improves cancer detection rates but that it does increase recall rates in screening programs for breast cancer [15].…”
Section: Introductionmentioning
confidence: 99%